Interpersonal coordination tendencies supporting the creation/prevention of goal scoring opportunities in futsal - Vilar, L.; Araújo, D.; Davids, K.; Travassos, B.; Duarte, R.; Parreira, J. (European Journal of Sport Science, 2014)
Research on 1vs1 sub-phases in team sports has shown how one player coordinates his/her actions with his/her opponent and the location of a target/goal to attain performance objectives. In this study, we extended this approach to analysis of 5vs5 competitive performance in the team sport of futsal to provide a performance analysis framework that explains how players coordinate their actions to create/prevent opportunities to score goals. For this purpose, we recorded all 10 futsal matches of the 2009 Lusophony Games held in Lisbon. We analysed the displacement trajectories of a shooting attacker and marking defender in plays ending in a goal, a goalkeeper's save, and a defender's interception, at four specific moments during performance: (1) assisting attacker's ball reception and (2) moment of passing, (3) shooter's ball reception, and (4), shot on goal. Statistical analysis showed that when a goal was scored, the defender's angle to the goal and to the attacker tended to decrease, the attacker was able to move to the same distance to the goal alongside the defender, and the attacker was closer to the defender and moving at the same velocity (at least) as the defender. This study identified emergent patterns of coordination between attackers and defenders under key competitive task constraints, such as the location of the goal, which supported successful performance in futsal.